Property and microstructure of aluminosilicate inorganic coating for concrete: Role of water to solid ratio. (1st September 2017) - Mu, Song; Liu, Jiaping; Lin, Wei; Wang, Yaocheng; Liu, Jianzhong; Shi, Liang; Jiang, Qian
Highlights: Increased ratio of water to solid (W/S) decreased viscosity of geopolymer coating. Pore volume of 30–50 nm increased with the increasing W/S at 28-day age. Increased W/S resulted in an inverse change of polycondensation degree. Optimal W/S improved the coating properties. Abstract: As a potential matrix of inorganic coating, aluminosilicate geopolymer has excellent properties of low Volatile Organic Compounds (VOC) emission, anticorrosion and long life. However, little concern has been devoted to basic parameters of the aluminosilicate geopolymer coating. The present paper investigated the influence of water to solid ratio on the property and microstructure of the coating. Results showed that as the water to solid ratio of geopolymer coating increased from 0.8 to 1.0, the hardening process was delayed significantly. The variation of autogenous shrinkage differed from that of drying shrinkage. The overall porosity measured by Mercury Intrusion Porosimetry (MIP) decreased, while a dramatic increased volume of pores with the size of 30–50 nm was detected. Besides, the Fourier Transform Infrared Spectroscopy (FTIR) results indicated that polycondensation degree was affected in an inverse manner at early and late ages of geopolymer hardening.